2015
DOI: 10.1111/all.12582
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of health-related quality of life of European food-allergic patients

Abstract: In this study, food allergy-related HRQL may be predicted to a greater extent in adults than in children. Allergy to certain foods may cause greater HRQL impairment than others. Country of origin may affect HRQL, at least in children. Experiencing anaphylaxis or being prescribed an EAI has no impact on HRQL in either adults or children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 30 publications
(50 reference statements)
3
54
0
1
Order By: Relevance
“…We also observed that the level of avoidance, as well as comorbidities (AD AE asthma), was linked to anxiety and consequently to the quality of life. In contrast, a history of severe reaction was surprisingly not linked to anxiety, as has previously been discussed in the literature [34,35]. Overall, this raises the question of the criteria associated with dietary advice about PAL, which deserve to be clarified.…”
Section: Dietary Advice By the Allergists Patient Anxietymentioning
confidence: 79%
“…We also observed that the level of avoidance, as well as comorbidities (AD AE asthma), was linked to anxiety and consequently to the quality of life. In contrast, a history of severe reaction was surprisingly not linked to anxiety, as has previously been discussed in the literature [34,35]. Overall, this raises the question of the criteria associated with dietary advice about PAL, which deserve to be clarified.…”
Section: Dietary Advice By the Allergists Patient Anxietymentioning
confidence: 79%
“…Forty to sixty percent of children with milk or egg allergy will outgrow their food allergy until the age of 6 years (100, 101), whereas this occurs at a lower rate in children with allergy to peanut or tree nuts. These individuals may be considered prototypic for tolerance acquisition after established potentially life-threatening food allergy (100,(102)(103)(104)(105). The sequence of events and biomarkers that define individuals with persistent food allergy and those who outgrow their food allergy remain unclear.…”
Section: Oral and Sublingual Immunotherapy In Food Allergymentioning
confidence: 99%
“…Validated health‐related quality of life (HRQL) instruments are available for children, adolescents, and adults with food allergies and for their parents or caregivers . Interestingly, one study on HRQL showed that experience of anaphylaxis had limited impact on HRQL; it also found that allergies to fish and milk in adults and peanuts and soy in children caused greater HRQL impairment as compared to other foods . A prospective cohort study examining food allergy‐associated quality of life found that performing a food challenge improved the quality of life irrespective of the outcome of the challenge .…”
Section: Quality Of Lifementioning
confidence: 99%